Dust Deposition and Associated Heavy Metal Contamination in the Neighborhood of a Cement Production Plant at Konongo, Ghana - Prince Baffour Awuah; Albert Amatey Adjaottor; Emmanuel Gikunoo; Emmanuel Kwesi Arthur; Frank Ofori Agyemang; Douglas Siaw Baah (Journal of Chemistry)
The release of harmful particles from industries is one of the important sources of environmental pollution worldwide. The goal of this study was to determine the amounts of dust deposition and heavy metal pollution in the soils surrounding a cement mill in Konongo, Ghana. Topsoils (0-10 cm) were sampled at the four geographical axes of the factory within a radius of 400 m, while at the same time, about 500 g of cement was sampled with a hand trowel. A Frisbee dust sampler was used to examine the levels of dust depositions at the various geographical axes of the factory. The heavy metals such as cadmium (Cd), chromium (Cr), copper (Cu), zinc (Zn), and lead (Pb) were measured in a total of 20 soil samples using atomic absorption spectroscopy (AAS). The results obtained for climatic elements such as wind speed and direction, temperature, and relative humidity were 2.25, 25.7, and 49.5 m3/s, respectively. The average deposition of dust within the study period using the geographical axis indicated that the southern axis recorded the highest dust accumulation with a mean of 60.2 g/m2 per month. The mean concentrations of metals at the various axes were 1.04 mg/kg, 4.78 mg/kg, 8.95 mg/kg, 9.30 mg/kg, and 18.4 mg/kg for Cd, Cr, Cu, Zn, and Pb, respectively. The concentration of chemical components investigated in the soil was below the WHO/FAO standard, except for Cd. The spatial distribution pattern of the examined heavy metals showed that Cd, Cr, and Cu represent possible sources of soil contaminants. According to the conclusions of this research, this paper suggests an approach to investigate the areas contaminated with heavy metals to call out the attention of local authorities to take action.